(untitled) (Research, Society and Development, 2022)
The present study aims to identify the scientific production supported by the Theory of Social Representations (TRS) on Quality of Life and Temporomandibular Disorders. The sample consisted of 11 articles, produced with the theme, and these were analyzed by the Iramuteq software, using the Reinert Method, from the Descending Hierarchical Classification (CHD) and the Similitude Analysis (SA). The results of the lexical analysis of the corpus presented six classes: (i) Conceptions about temporomandibular disorders; (ii) Symptoms or Signs related to temporomandibular disorders, (iii) Diagnosis of Temporomandibular Disorders; (iv) Specific exams for Temporomandibular Disorders; (v) Consequences of Temporomandibular Disorders; and (vi) Causes related to temporomandibular disorders. In the similarity analysis, the social representation of temporomandibular disorders was objectified in experiencing the dysfunction, pain, disease, fear, strategy, indicating the psychosocial aspects that are representative of the illness. Pain was the figurative element of objectification, anchored by psycho-emotional factors. According to social actors, adverse feelings such as performing academic activities, tests, figured as characteristics and psychosocial implications not yet measured in the long term. It is hoped that the result of this study will contribute to a better understanding of Temporomandibular Disorders.